The impact of heating on the unfolding and polymerization process of frozen-stored gluten. (December 2018) - Wang, Pei; Zou, Min; Tian, Mengqi; Gu, Zhenxin; Yang, Runqiang
Abstract: Gluten deterioration is the main factor for the degraded quality of frozen dough. Previous studies comprehensively elucidated the degradation mechanism of gluten during frozen storage, however, the subsequent polymerization process of frozen-stored gluten remains largely unelucidated. The current study comparatively investigated the effects of heating on the unfolding and polymerization process of fresh and frozen-stored gluten from molecular weight, subunit composition, non-covalent interactions, secondary structure, surface hydrophobicity and microstructure. The results showed that frozen storage degraded the polymerization of gluten during heating by weakening the polymerization ability of both gliadin and glutenin. Glutenin monomers were more sensitive, while γ-gliadins were less sensitive to polymerize upon heating for frozen gluten as compared with that of the fresh gluten. Frozen storage could impede the unfolding process at the initial heating stage for frozen gluten: the ordered α-helices in frozen gluten was significantly higher than that of fresh gluten during heat treatment, and the surface hydrophobic groups were more buried than fresh gluten. The microstructure analysis suggested that the ruptured frozen gluten network was more sensitive to shrink than the fresh gluten network during the initial heating at 50 °C and further formed denser and thicker pore walls when the temperature exceeded 70 °C. The results of this study may consummate the deterioration theory of frozen gluten quality from both freezing and heating stages, and thus providing a more comprehensive theoretical basis and technical support for the effective preservation of frozen dough quality. Graphical abstract: The suppressed formation of glutenin-gliadin crosslinking by weakened polymerization ability of glutenin and gliadin during heating of frozen-stored gluten. Highlights: The polymerization ability of glutenin and gliadin was weakened for frozen gluten. Glutenin monomers in frozen gluten were more prone to polymerize than the fresh one. γ-Gliadins in frozen gluten were less sensitive to polymerize than the fresh one. Unfolding process of frozen gluten was impeded compared with fresh one upon heating. Denser and thicker pore walls were formed in the heated frozen gluten.